Exploring women's experiences of participation in shared decision-making during childbirth: a qualitative study at a reference hospital in Spain - María López-Toribio; Paulina Bravo; Anna Llupià (BMC, 2021)
Abstract Background Women's engagement in healthcare decision-making during childbirth has been increasingly emphasised as a priority in maternity care, since it increases satisfaction with the childbirth experience and provides health benefits for women and newborns. The birth plan was developed as a tool to facilitate communication between health professionals and women in Spain, but their value in routine practice has been questioned. Besides, little is known about women's experiences of participation in decision-making in the Spanish context. Thus, this study aimed to explore women's experiences of participation in shared decision-making during hospital childbirth. Methods An exploratory qualitative study using focus groups was carried out in one maternity unit of a large reference hospital in Barcelona, Spain. Participants were first-time mothers aged 18 years or older who had had a live birth at the same hospital in the previous 12 months. Data collected were transcribed verbatim and analysed using a six-phase inductive thematic analysis process. Results Twenty-three women participated in three focus groups. Three major themes emerged from the data: "Women's low participation in shared decision-making", "Lack of information provision for shared decision-making", and "Suggestions to improve women's participation in shared decision-making". The women who were willing to take an active role in decision-making encountered barriers to achieving this and some women did not feel prepared to do so. The birth plan was experienced as a deficient method to promote women's participation, as health professionals did not use them. Participants described the information given as insufficient and not offered at a timely or useful point where it could aid their decision-making. Potential improvements identified that could promote women's participation were having a mutually respectful relationship with their providers, the support of partners and other members of the family and receiving continuity of a coordinated and personalised perinatal care. Conclusion Enhancing women's involvement in shared decision-making requires the acquisition of skills by health professionals and women. The development and implementation of interventions that encompass a training programme for health professionals and women, accompanied by an effective tool to promote women's participation in shared decision-making during childbirth, is highly recommended.